Assessment of genetically modified maize MON 89034 × 1507 × NK603 × DAS‐40278‐9 and subcombinations independently of their origin for food and feed uses, import and processing, under Regulation (EC) No 1829‐2003 (application EFSA‐GMO‐NL‐2013‐112). (16th January 2019) - ,; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Maize MON 89034 × 1507 × NK603 × DAS‐40278‐9 (four‐event stack maize) was produced by conventional crossing to combine four single events: MON 89034, 1507, NK603 and DAS‐40278‐9. The GMO Panel previously assessed the four single events and four of their subcombinations and did not identify safety concerns. No new data on the maize single events or their four subcombinations that could lead to modification of the original conclusions on their safety have been identified. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicates that the combination of the single maize events and of the newly expressed proteins in the four‐event stack maize does not give rise to food/feed safety and nutritional concerns. The GMO Panel concludes that the four‐event stack maize, as described in this application, is as safe as and nutritionally equivalent to its non‐GM comparator and the non‐GM reference varieties tested. In the case of accidental release of viable grains of the four‐event stack maize into the environment, this would not raise environmental safety concerns. The GMO Panel assessed the likelihood of interactions among the single events in the six maize subcombinations for which no experimental data were provided, and concludes that these are expected to be as safe as and nutritionally equivalent to the single events, the previously assessed subcombinations and the four‐event stack maize. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of the four‐event stack maize. No post‐market monitoring for food/feed is necessary. The GMO Panel concludes that the four‐event stack maize and its subcombinations are as safe as its non‐GM comparator and the tested non‐GM reference varieties with respect to potential effects on human and animal health and the environment.